First colour book penulis, Jane Buckley and Helen Ferguson ; ilustrator, Mandy Stanley ; alih bahasa, Prella Handarani Munandar ; editor, Margaratha hutauruk Eddy - BUCKLEY, Jane; Ferguson, Helen; Stanley, Mandy; Munandar, Prelia Handarani; Eddy, Margaretha Hutauruk (Erlangga, 2003)
47 hlm ilus 31 cm